Potensi konflik dan pembentukan modal sosial: belajar dari sebuah desa transmigran di Kalimantan Timur - Sukapti Wartiharjono (Faculty of Social and Political Science, Universitas Airlangga, 2017)
Conflicts caused by differences in cultural backgrounds and competition over natural resources among social groups in the project areas of transmigrations in Indonesia are not uncommon occurrences. This paper seeks to explore two aspects pertaining to this issue: (1) social conflict potentials among transmigrant communities particularly those between local transmigrants and the inter island transmigrants; and (2) the formation of social capital as an instrumental power in achieving and sustaining harmonious social relationship in the area in question. The research on the two subjects was a qualitative field research. In-depth interview and observation were employed in gathering data. The research had led to the finding that the conflict potentials in the observed transmigrant area were related to land distribution among transmigrant households and access to economic resources. Nonetheless, the conflict potentials did not inhibit the formation of social capital that bound all the members of the society. The result of the observation showed that a social trust has been constructed among the transmigrant settlers based on the value of cooperation or working together formutual benefit both in the daily interactions in the settlement area and in the plantation management activities. The prevalent social trust has prevented open conflict from breaking out among different ethnic social groups and hencecreated harmonious social relations